Teaching Mathematics with a Dual Analysis and Synthesis Strategy and its effect in developing Scientific Inquiry Skills among Secondary Stage Students in the State of Kuwait - Alshamari, Mshari Matar; Alzou’bi, Abdullah Salem (Arab Journal for Sciences and Research Publishing, 2022)
This study aimed to investigate the effect of Teaching Mathematics with a Dual Analysis and Synthesis Strategy and its effect in developing Scientific Inquiry Skills and Mathematical Logical Thinking among Secondary Stage Students in the State of Kuwait. The algebra unit of the study members, and the development of the logical-mathematical thinking skills test consisted of (8) questions. The study was applied to Al-Shujaa Ibn Al-Aslam Secondary School for Boys, affiliated to Al-Farwaniyah Educational District, and two divisions were appointed from the tenth grade people, from the school year 2021/2022 AD, one of them representing the experimental group, which included (30) students, and the other division represented the control group, which included (30). a student. The study concluded that there is a statistically significant effect of teaching mathematics with a binary strategy of analysis and synthesis on scientific inquiry among secondary school students in the State of Kuwait.
Keywords: Scientific Inquiry; A Dual Analysis and Synthesis Strategy; Algebra; Mathematics